Social Norms and Fertility - Sunha Myong; JungJae Park; Junjian Yi (Institute of Labor Economics (IZA), 2018)
We first document three stylized facts about marriage and fertility in East Asian societies: They have the highest marriage rates in the world, but the lowest total fertility; they have the lowest total fertility, but almost all married women have at least one child. By contrast, almost no single women have any children. We then explain these three facts, focusing on two social norms associated with Confucianism: the unequal gender division of childcare within a household and the stigma attached to out-of-wedlock births. We incorporate the two social norms into an economic model, and structurally estimate it using data from South Korea's censuses and household surveys. We find that, on the one hand, the social norm of unequal gender division of childcare significantly contributes to the low fertility of South Korea, and its effect varies across education: The social norm lowers fertility for highly educated women but increases it for the less educated. Pro-natal policies can increase average fertility, but they are not effective in mitigating the role of this norm as they cannot sufficiently boost fertility for highly educated women. On the other hand, the social stigma has negligible effects on marriage and fertility. Historical simulation results show that fertility would have decreased less dramatically in the absence of the first norm, especially for younger birth cohorts. Our results suggest that the tension between the persistent gender ideology and rapid socioeconomic development is the main driving force behind the unique marriage and fertility patterns of East Asian societies, and that this tension has escalated in recent decades.
Keywords: J11; J12; J13; 330; Confucianism; social norms; fertility; demographic transition; East Asia societies